Compliance to iron and folic acid supplementation and associated factors among antenatal mothers attending OPD in a tertiary care institute in India - B., Athira; Rai, Priyanka; Vasantha Kalyani, C.; Verma, Bhavna (International Journal Of Community Medicine And Public Health, 2024)
Background: Anaemia in pregnancy is a serious health issue faced globally by all countries. Noncompliance to iron and folic acid supplement plays a role in the high prevalence of anemia in pregnant women. Objectives: The objectives were to find out the proportion of compliance to iron and folic acid tablets (IFA) among antenatal mothers and to determine factors associated with it. Methods: A cross sectional study was conducted among 260 antenatal mothers attending antenatal clinic in a tertiary care hospital in Jharkhand from August 2023 to February 2024. Subjects were recruited through consecutive sampling. A pretested, predesigned, semi structured interview schedule was used to collect information. Data were analyzed using SPSS 15.0. Chi square was used to find out the association of compliance with independent variables. P value of <0.05 was considered as significant. Results: Among the study participants, majority (55.7%) were above 26 years’ age and 60% stayed in rural area. Overall, 64.2% stayed in joint family. The proportion of compliance to IFA among antenatal mothers was 58.8% (n=153), and the reason for noncompliance (n=107) in the majority was forgetfulness (46.7%) followed by “side effects” (28%). Factors like socio economic status and type of family have shown significant association with this compliance. Conclusions: This study highlighted that only around half of the pregnant women are compliant with IFA, and this situation demands for information education and communication activities to generate awareness.